Predictive utility of cardiac ultrasound in traumatic cardiac arrest in a combat casualty. Issue 1 (3rd March 2015) - Kinnear-Mellor, Rex; Newton, K; Woolley, T; Rickard, R
Abstract : We report a case of traumatic cardiac arrest in a combat casualty who was resuscitated to return of spontaneous circulation despite asystole and no visible cardiac activity on initial ultrasound examination. This return of spontaneous circulation suggests that survival may be possible in traumatic cardiac arrest due to exsanguination, even when there is no demonstrable cardiac activity on ultrasound. Cardiac ultrasonography was performed for 10 s only. We suggest that cardiac ultrasonography should be performed for a minimum of 1 min during volume resuscitation. If absence of cardiac activity is confirmed once the heart is full, and there are no other signs of life (including pupillary reaction), then termination of resuscitation should be considered.